Young age is a key determinant of body weight gain after switching from tenofovir disoproxil fumarate to tenofovir alafenamide in Japanese people living with HIV. Issue 2 (February 2023) - Sekiya, Ryoko; Muramatsu, Takashi; Ichiki, Akito; Chikasawa, Yushi; Bingo, Masato; Yotsumoto, Mihoko; Hagiwara, Takeshi; Amano, Kagehiro; Kinai, Ei
Abstract: Background: Treatment with tenofovir alafenamide fumarate (TAF) is associated with body weight gain. However, little or no information is available on this issue in Asian populations. Methods: This single-center retrospective study included Japanese people living with HIV (PLWH) who satisfied the following criteria; 1) switching from TDF to TAF after HIV-suppression, 2) follow-up for ≥2 years while on TDF and TAF, and 3) no switching of the third antiretroviral agent. Changes in annual body weight and lipid profiles were compared between the TDF and TAF periods. Results: Of 328 patients, dolutegravir (DTG) was used in 118 PLWH. Overall, no significant difference in weight gain was observed between TDF and TAF (0.76 vs. 0.9 kg/year, p = 0.331). In TAF-period, younger (<50 years of age) group showed significantly greater weight gain than older group (1.03 vs. 0.12 kg/year, p = 0.037). In DTG group, weight gain was larger in TAF-period (0.74 vs. 1.31 kg/year, p = 0.046), especially in younger subgroup (1.43 kg/year) compared with older one (−0.12 kg/year). Multivariate regression analysis showed that TAF was not associated with weight gain (estimates 0.201, p = 0.170) except for DTG group, whereas young age was associated with weight gain in all subjects (estimates −0.033/1 year older, p < 0.001), DTG, RAL, and EFV groups. Conclusion: In Japanese PLWH, annual body weight change was comparable in TDF- and TAF-period, while TAF plus DTG correlated with weight gain. Since young age was a key determinant of weight change, careful interpretation is needed for TAF-associated weight gain.